More rain, less soil: long‐term changes in rainfall intensity with climate change. Issue 4 (21st December 2015) - Burt, Tim; Boardman, John; Foster, Ian; Howden, Nicholas
Abstract: This commentary discusses the role of long‐term climate change in driving increases in soil erosion. Assuming that land use and management remain effectively constant, we discuss changes in the ability of rainfall to cause erosion (erosivity), using long daily rainfall data sets from southeast England. An upward trend in mean rainfall per rain day is detected at the century‐plus timescale. Implications for soil erosion and sediment delivery are discussed and evidence from other regions reviewed. We conclude that rates of soil erosion may well increase in a warmer, wetter world. Copyright © 2015 John Wiley & Sons, Ltd.